Ba6In2Ge2Te15: a THz birefringent material with an intriguing quasi-[Te5]4− chain possessing large optical anisotropy and an ultrawide transmission range. Issue 14 (9th June 2022) - Sun, Mengran; Zhang, Xingyu; Xing, Wenhao; Uykur, Ece; Yin, Wenlong; Lin, Zheshuai; Yao, Jiyong
Abstract : Ba6 In2 Ge2 Te15, a THz birefringent material with an intriguing quasi-[Te5 ] 4− chain, was successfully synthesized. Experimental and theoretical results illustrate that Ba6 In2 Ge2 Te15 exhibits large birefringence and ultrawide transparency windows. Abstract : Exploring mid- and far-infrared (MFIR) and even terahertz (THz) birefringent crystals with large optical anisotropy remains a great challenge. Herein, a novel THz birefringent material Ba6 In2 Ge2 Te15, which contains the intriguing quasi-[Te5 ] 4− chain, has been successfully synthesized and investigated. This compound displays an ultrawide transparent region (1.3–40.2 μm), exhibiting high transmittance from NIR to MFIR and even THz regions. Moreover, the birefringence of Ba6 In2 Ge2 Te15 equals 0.377@30–42 μm (7.1–10 THz) and 0.42@2.09 μm, which are larger than those of most of the reported chalcogenides, both properties surpassing commercial birefringent crystals YVO4 and TiO2 . Furthermore, the first-principles calculations demonstrate that the large optical anisotropy originates from the non-bonded p orbitals of Te atoms in the quasi-[Te5 ] 4− chains. This work might shed light on the follow-up design and exploration of THz birefringent materials.